Optimizing the Performance of the Kamsel Unit Through Dikmas Traffic in Minimizing the Number of Traffic Violations Among High School Students at Polrestabes Semarang - Faturrahman, Ahmad Dzakky (Advances in Police Science Research Journal, 2024)
The number of traffic violations at the Semarang Polrestabes from 2019 to 2021 is unstable, due to the number of traffic violations that fell in 2020 and then rose again in 2021. With the dominance of offenders, namely high school students. SMA students in the Semarang Polrestabes jurisdiction are always the highest every year compared to other professions. In terms of driving, there are still many high school students in the Semarang Polrestabes area who do not understand about good and correct driving procedures and ideal vehicle conditions. Most of these high school students can only drive vehicles without knowing proper and correct driving procedures. This is a major factor in the occurrence of traffic violations at the Semarang Polrestabes. The author limits the scope of the writing focus by focusing on the object under study so that the problems discussed do not widen and the author uses a qualitative method in which the author focuses on problems that occur in the Kamsel unit’s efforts in implementing community education to minimize the number of traffic violations in the jurisdiction of the Semarang Polrestabes . Judging from the data that the author gets, in the jurisdiction of the Semarang Polrestabes there are still many traffic accidents which occur due to the large number of traffic violations as well. In the application of this qualitative method, the author examines directly into the field, but not all events in the field are studied, only problems related to the object being examined by the author. The author applies the concepts and theories that have been explained previously where these concepts and theories will assist the author’s analysis in focusing and discussing the problems that are divided into issues discussed by the author.